2021
DOI: 10.3390/cells10123586
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutational Profile of High-Grade Serous Ovarian Carcinoma and Triple-Negative Breast Carcinoma in Young and Elderly Patients: Similarities and Divergences

Abstract: Background: Triple-negative breast cancer (TNBC) and High-Grade Serous Ovarian Cancer (HGSOC) are aggressive malignancies that share similarities; however, different ages of onset may reflect distinct tumor behaviors. Thus, our aim was to compare somatic mutations in potential driver genes in 109 TNBC and 81 HGSOC from young (Y ≤ 40 years) and elderly (E ≥ 75 years) patients. Methods: Open access mutational data (WGS or WES) were collected for TNBC and HGSOC patients. Potential driver genes were those that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 79 publications
0
7
0
1
Order By: Relevance
“…From a clinical point of view [11,17,18] the most relevant GAs were: ESR1 (mutation, n = 1; as already described), RB1 (mutation, n = 2), CCNE1 (CNG, n = 5), FGFR1 (CNG, n = 5) and PIK3CA (mutation, n = 6; as stated before). Other GAs of clinical interest due to possible ineffectiveness [11,[19][20][21][22] detected in our collective are: NF1 (CNL, n = 5), AR (CNG, n = 4), CDK6 (CNG, n = 4), MET (CNG, n = 3), ERBB2 (mutation, n = 2; as speci ed above), LRP1B (CNL, n = 2) and FGFR2 (CNG, n = 1) (see Fig. 3).…”
Section: Gas Indicating Ineffectiveness or Safety Concerns According ...mentioning
confidence: 70%
“…From a clinical point of view [11,17,18] the most relevant GAs were: ESR1 (mutation, n = 1; as already described), RB1 (mutation, n = 2), CCNE1 (CNG, n = 5), FGFR1 (CNG, n = 5) and PIK3CA (mutation, n = 6; as stated before). Other GAs of clinical interest due to possible ineffectiveness [11,[19][20][21][22] detected in our collective are: NF1 (CNL, n = 5), AR (CNG, n = 4), CDK6 (CNG, n = 4), MET (CNG, n = 3), ERBB2 (mutation, n = 2; as speci ed above), LRP1B (CNL, n = 2) and FGFR2 (CNG, n = 1) (see Fig. 3).…”
Section: Gas Indicating Ineffectiveness or Safety Concerns According ...mentioning
confidence: 70%
“…In the other three cases, endocrine therapy was combined with either a CDK4/6 inhibitor or fulvestrant or HER2targeted therapy when the subtype changed during the course of the disease, and therefore probably showed a good effect of the respective therapy. Other GAs of clinical interest due to possible ineffectiveness [11,23,24,25,26] detected in our collective are: NF1 (CNL, n = 5), AR (CNG, n = 4), CDK6 (CNG, n = 4), MET (CNG, n = 3), HER2 (mutation, n = 2; as specified above), LRP1B (CNL, n = 2) and FGFR2 (CNG, n = 1) (see ▶ Fig. 2).…”
Section: Gas Indicating Ineffectiveness or Safety Concerns According ...mentioning
confidence: 74%
“…A study of Thai TNBC patients has reported KMT2C to be among the most frequently mutated genes in this population, found in 57.76% ( n = 116) of all cases [ 68 ]. In a study by Serio et al, KMT2C was among the 15 most altered genes and was more frequently altered in elderly TNBC patients (26%, n = 22) than in young patients [ 69 ]. Li et al investigated tissue samples of 17 Chinese TNBC patients with special morphologic patterns (STs).…”
Section: Discussionmentioning
confidence: 99%